Implementasi Pemidanaan Pelaku Penyertaan (Deelneming) Tindak Pidana Korupsi - Prasetiono, Yogi; Arifin, Zaenal; Sudarmanto, Kukuh (Universitas Semarang, 2022)
This scientific article aims to discuss the implementation, obstacles and solutions for criminalizing the perpetrators of corruption in the Semarang District Court No. 41/Pid.Sus-TPK/2020/PN Smg. This type of research is normative juridical with a case approach, descriptive analytical specifications. The data used is secondary data, which is taken by means of literature study and study documentation which is then analyzed qualitatively. The results of the study indicate that in imposing the severity of the punishment for the perpetrators of participating (deelneming) in the corruption., the Panel of Judges has not fully considered who the main perpetrators or participants. Meanwhile, the obstacles faced regarding the understanding and interpretation of the Panel of Judges in qualifying the actors and doing so only limited to stating the existence of a collective cooperative relationship, resulting in the invisible role, position and pattern of the relationship of the actors. Again, by not withdrawing the relevant parties in the incident due to the lack of complete and clear accusations/Public Prosecutors in adding additional, so that the difficulty in revealing the value of state financial losses in the central procurement of Operating Room Systems at RSUD Dr. Soehadi Prijonegoro, Sragen Regency, which was caused by corruption crimes committed by the. Against these obstacles, the Panel of Judges must be able to make breakthroughs through quality decisions and reflect a sense of justice for the community in order to achieve justice, certainty and legal benefit. Artikel ini bertujuan mengkaji implementasi, kendala dan solusi pemidanaan pelaku penyertaan (deelneming) tindak pidana korupsi atas putusan Pengadilan Negeri Semarang Nomor 41/Pid.Sus-TPK/2020/PN Smg. Jenis penelitian ini adalah yuridis normatif dengan pendekatan kasus, spesifikasi deskriptif analitis. Hasil penelitian menunjukkan bahwa dalam menjatuhkan berat ringannya pemidanaan pelaku penyertaan (deelneming) perkara tindak pidana korupsi, Majelis Hakim belum mempertimbangkan secara lengkap mengenai siapa pelaku utama maupun turut sertaSedangkan kendala yang dihadapi mengenai pemahaman dan penfsiran Majelis Hakim dalam mengkualifikasikan pelaku turut serta melakukan hanya sebatas menyatakan adanya hubungan kerjasama secara kolektif, mengakibatkan tidak terlihatnya peran, kedudukan maupun pola hubungan para pelaku. Ditambah lagi dengan tidak ditariknya pihak terkait dalam peristiwa tersebut akibat kurang cermat, lengkap dan jelas dakwaan Jaksa/Penuntut Umum dalam menyusun dakwaan, sehingga kesulitan dalam mengungkap kepastian pengembalian nilai kerugian keuangan negara pada kegiatan Pengadaan Sentral OK/Room Operation System pada RSUD Dr. Soehadi Prijonegoro Kabupaten Sragen yang disebabkan oleh tindak pidana korupsi yang dilakukan oleh para terdakwa. Terhadap kendala-kendala tersebut, Majelis Hakim harus mampu membuat terobosan hukum melalui putusan yang berkualitas dan mencerminkan rasa keadilan bagi masyarakat demi tercapainya keadilan, kepastian dan kemanfaatan hukum.